Alloyed Pt3M (M = Co, Ni) nanoparticles supported on S- and N-doped carbon nanotubes for the oxygen reduction reaction - Louisia Stéphane; Thomas Yohann R J; Lecante Pierre; Heitzmann, Marie; Rosa, Axet M; Pierre-André, Jacques; Serp Philippe (Beilstein journal of nanotechnology, 2019)
Sulfur- (S-CNT) and nitrogen-doped (N-CNT) carbon nanotubes have been produced by catalytic chemical vapor deposition (c-CVD) and were subject to an annealing treatment. These CNTs were used as supports for small (≈2 nm) Pt3M (M = Co or Ni) alloyed nanoparticles that have a very homogeneous size distribution (in spite of the high metal loading of ≈40 wt % Pt), using an ionic liquid as a stabilizer. The electrochemical surface area, the activity for the oxygen reduction reaction and the amount of H2O2 generated during the oxygen reduction reaction (ORR) have been evaluated in a rotating ring disk electrode experiment. The Pt3M/N-CNT catalysts revealed excellent electrochemical properties compared to a commercial Pt3Co/Vulcan XC-72 catalyst. The nature of the carbon support plays a key role in determining the properties of the metal nanoparticles, on the preparation of the catalytic layer, and on the electrocatalytic performance in the ORR. On N-CNT supports, the specific activity followed the expected order Pt3Co > Pt3Ni, whereas on the annealed N-CNT support, the order was reversed.